Immunodiagnosis and Immunotherapeutics Based on Human Papillomavirus for HPV-Induced Cancers - Dong, Zhen; Hu, Renjian; Du, Yan; Tan, Li; Li, Lin; Du, Juan; Bai, Longchang; Ma, Yingkang; Cui, Hongjuan (Frontiers in Immunology, 2021)
Infection of human papillomavirus (HPV) is one of the main cause of malignant neoplasm, especially cervical, anogenital, oropharyngeal cancers. Although we have developed preventive vaccines which can avoid HPV infection. However, there are still many new cases of HPV-related cancers worldwide. Therefore, early diagnosis and therapy are important for the treatment of these diseases. As HPVs are the major contributors of these cancers, it is reasonable to development reagents, kits or devices that to detect and eliminate HPVs for the early diagnosis and therapeutics. Immunology is a precise method that are promising for the accurate detection and blockade of HPVs. During last decades, the mechanisms of how HPVs induce neoplasm have been extensively elucidated, and several oncogenic HPV early proteins including E5, E6 and E7 have been shown to be positively related to the oncogenesis and malignancy of HPV-induced cancers. These oncoproteins are promising biomarkers and therapeutical targets for the diagnosis and therapy of HPV-related cancers. Importantly, many specific monoclonal antibodies (mAbs) or newly designed antibody mimics as well as immunological new kits, devices and reagents are developed for both the immunodiagnosis and immunotherapeutics of HPV-induced cancers. In the current review, we summarize the research progress in the immunodiagnosis and immunotherapeutics based on HPV for HPV-induced cancers. Especially, we depict the most promising serological methods for the detection of HPV infection and several therapeutical immunotherapeutics based on HPV, using immunological tools including native mAbs, radio-labelled mAbs, affitoxins (affibody-linked toxins), intracellular single-chain antibodies (scFvs), nanobodies and therapeutical vaccines. Our review is aimed to provide new clues for researchers to develop novel strategies and methods for the diagnosis and treatment of HPV-induced tumors.